Perlindungan Hukum Bagi Anak Sebagai Korban Kekerasan Seksual Incest Dalam Perspektif Viktimologi - Saputri, Berliana Gina; Siswanto, Siswanto; Khamim, Mohammad; Pratama, Erwin Aditya; Mukhidin (Universitas Pancasakti Tegal, 2025)
Sexual violence is an act of coercion by the perpetrator on his victim. Children as victims suffer mental loss that is disturbed and has excessive fear. this violence occurs in the private sphere (family), even though the family sphere is always considered as a safe place for children. Based on this, it can be drawn what are the factors that cause the occurrence of rape against children in the family sphere (incest) and how efforts in the protection of the law against children as incest victims according to the perspective of Viktimology. This research method uses normative research , the purpose of this research is to find out the factors that cause sexual violence in children and also to know what efforts can be given in child protection. The result of the discussion that the causative factor consists of two factors, namely the external and internal factors. Factors of close relationship between victims and perpetrators can be the cause of sexual violence. As for environmental factors that are not good can be one of the other factors. Therefore, it is necessary to protect the child so that the child receives his rights and what the child needs. In Law No. 23 of 2002 on Child Protection has regulated the rights of children.